Measurement of sensitivity on vigilance experiments: Statistical consequences from the use of indices based on signal detection theory - Manuel J. Blanco (Psicológica, 2001)
Vigilance and Signal Detection Theory. This article assesses theextent to which the sensitivity decrement over time frequently observed invigilance tasks can be affected by the index or statistic used to measure thesensitivity. The paper reports the results of a simulation of sensitivitydecrement in vigilance tasks using two measures of sensitivity, d and A.The results of these simulations indicate that the sensitivity decrement issomewhat larger for d than for A, and that probability to obtain asignificant decrement in an analysis of variance of the data is also higher ford than for A.